2006
DOI: 10.1002/poc.1050
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and mechanistic studies on sulfamate esters: models of enzyme inhibitors

Abstract: Many compounds containing a sulfamate moiety, such as NH 2 SO 2 O-are now known to be medicinally important. However, very little is known about their mechanisms of reaction even under non-biological conditions. In this work the various types of elimination mechanisms that may occur have been probed by studying the kinetics of the reactions of model sulfamate substrates with amines (bases) that act as models for the enzymes involved. The principal mechanistic tool employed has been Brönsted plots and both 'nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…Compound 1a was the substrate mainly used in this study. The p K a for the ionization of 1a was found to be 17.9, in excellent agreement with a value of 17.8 previously determined in this laboratory 10. The p K a value for the second ionization gave an average value of 21.08 in ACN on the basis of three determinations by using two different analytical wavelengths.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Compound 1a was the substrate mainly used in this study. The p K a for the ionization of 1a was found to be 17.9, in excellent agreement with a value of 17.8 previously determined in this laboratory 10. The p K a value for the second ionization gave an average value of 21.08 in ACN on the basis of three determinations by using two different analytical wavelengths.…”
Section: Resultssupporting
confidence: 88%
“…Over much the same period of time, we have been investigating the hydrolysis and aminolysis mechanisms of various esters such as 4‐nitrophenyl methylsulfamate, 4‐nitrophenyl benzylsulfamate and a series of 4‐nitrophenyl phenylsulfamates 8,9. Latter studies have focussed more on 4‐nitrophenyl sulfamate NH 2 SO 2 OC 6 H 4 ‐NO 2 ‐4 ( 1a ), because this compound could act as a simple model for the more complex and therapeutically important esters 10. The thrust of this current work is to examine the kinetics and mechanism of reaction in acetonitrile (ACN) of compound 1a and five other phenyl sulfamate derivatives, 1b – f .…”
Section: Introductionmentioning
confidence: 99%
“…The values of pK BH + of the substituted sultams = 5.96–8.3 . Sulfamate esters have pK a values of ≈ 8 in water‐organic media . Sulfamides have two electron donor nitrogen atoms.…”
Section: Resultsmentioning
confidence: 95%
“…[26] Sulfamate esters have pK a values of ≈ 8 in water-organic media. [51] Sulfamides have two electron donor nitrogen atoms. So protonation of the sulfamides might take place on nitrogen as observed for the sultams [52] and sulfinamides.…”
Section: Resultsmentioning
confidence: 99%
“…The Brønsted-type plot was biphasic, the break point at pK a ≈ 18.2 more or less corresponding to the pK a of the ester (109) (17.8). The proposed mechanism (Scheme 30) involves a sequential double deprotonation of (109) leading first, via (110), to the sulfenamine (112) and at higher basic strength to (111) and thence to a novel anionic sulfenamine (113), the products in each case being an N ,N -dialkylsulfamide (114) and p-nitrophenol. 114 Theoretical studies of the hydrolysis of N -benzyl-3-oxo-β-sultam (115) showed that the activation energies for the pathways leading to the products of C-N and S-N cleavage for the uncatalysed hydrolysis were very similar.…”
Section: (Iv) Thiophosphatesmentioning
confidence: 99%